Experimental and numerical study of high strain rate property of pure copper processed by ECAE method - Sulaiman, S.; Nemati, J.; Majzoobi, G. H.; AlJermi, M. (Taylor and Francis, 2019)
In the present study, the impact strength of refined grain pure copper developed by equal channel angular extrusion, up to eight passes at room temperature following route A with a constant ram speed of 20 mm/min through a die angle of 90° between the die channels was investigated. The impact strength of extruded specimens is evaluated for the as-received and the extruded specimens after four and eight passes at a strain rate of 1200 s−1 using Split–Hopkinson pressure bartechniques by experiment and the finite element method simulation. A total increase in the ultimate strength and yield strength are 128% and 68%, respectively, and observed for the extruded material after eight passes. Optical microscopic examinations show a grain refinement from 32 to 4 µm. The results of the numerical study are consistent with that obtained from the experiment.